PENGARUH PEMBERIAN EKSTRAK RIMPANG KUNYIT (Curcuma domestica Val) TERHADAP KARDIOTOKSISITAS ASAP ROKOK PADA TIKUS PUTIH WISTAR - , NIDA UL MILLAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The increasing number of smokers have played an important role in the increase of cigarette smoke exposures at the environment. Cigarette smoke increases free radicals formation in the body. Turmeric having curcumin could act against free radicals. The heart is one of the vital organs affected by free radicals. In the present study, the effects of turmeric extract administration toward male albino Wistar rats + 3 months old exposed by cigarette smoke were determined. Twenty male Wistar rats were divided randomly into four groups of five each: Group I was given neither cigarette smoke exposure nor turmeric extract administration (control) (KI), Group II was given cigarette smoke exposure of 9 cigarettes/ day (KII), Group III was given 1 ml turmeric extract 0.25% (KIII) and Group IV was given cigarette smoke exposure of 9 cigarettes/ day and 1 ml turmeric extract 0.25% (KIV). After 2 months of treatment, necropsy was conducted to all rats and the heart samples were collected to be processed histopatologically and stained routinely with hematoxylin-eosin. Results of the present study indicated that the cigarette smoke caused heart lesions in KII such as cardiomyopathy marked by swollen and vacuolation, homogeneous eosinophilic cytoplasms, edema and necrosis of myocardia, and also congestion and mild hemorrhages (KII). Whereas, rats in Groups KI, KIII and KIV had normal histologic structures of myocardia. It is concluded, that turmeric extract could be a preventive herbs toward cardiotoxic effects of cigarette smoke. Further research has to be conducted to determine the anti cardiomyopathy mechanism of turmeric rhizome due to cigarette smoke exposure.